Church and Society in the Medieval North of England. - Dobson, R. B. (Bloomsbury Publishing, 1996)
English history has usually been written from the perspective of the south, from the viewpoint of London or Canterbury, Oxford or Cambridge. Yet throughout the middle ages life in the north of England differed in many ways from that south of the Humber. In ecclesiastical terms, the province of York, comprising the dioceses of Carlisle, Durham and York, maintained its own identity, jealously guarding its prerogatives from southern encroachment. In their turn, the bishops and cathedral chapters of Carlisle and Durham did much to prevent any increase in the powers of York itself. Barrie D.